Feasibility and acceptability of a technology-based, rural weight management intervention in older adults with obesity - Batsis, John A.; Petersen, Curtis L.; Clark, Matthew M.; Cook, Summer B.; Kotz, David; Gooding, Tyler L.; Roderka, Meredith N.; Al-Nimr, Rima I.; Pidgeon, Dawna; Haedrich, Ann; Wright, K. C.; Aquila, Christina; et al. (BMC geriatrics, 2021)
Background Older adults with obesity residing in rural areas have reduced access to weight management programs. We determined the feasibility, acceptability and preliminary outcomes of an integrated technology-based health promotion intervention in rural-living, older adults using remote monitoring and synchronous video-based technology. Methods A 6-month, non-randomized, non-blinded, single-arm study was conducted from October 2018 to May 2020 at a community-based aging center of adults aged ≥65 years with a body mass index (BMI) ≥30 kg/m 2 . Weekly dietitian visits focusing on behavior therapy and caloric restriction and twice-weekly physical therapist-led group strength, flexibility and balance training classes were delivered using video-conferencing to participants in their homes. Participants used a Fitbit Alta HR for remote monitoring with data feedback provided by the interventionists. An aerobic activity prescription was provided and monitored. Results Mean age was 72.9±3.9 years (82% female). Baseline anthropometric measures of weight, BMI, and waist circumference were 97.8±16.3 kg, 36.5±5.2 kg/m 2 , and 115.5±13.0 cm, respectively. A total of 142 participants were screened ( n =27 ineligible), and 53 consented. There were nine dropouts (17%). Overall satisfaction with the trial (4.7+ 0.6, scale: 1 (low) to 5 (high)) and with Fitbit (4.2+ 0.9) were high. Fitbit was worn an average of 81.7±19.3% of intervention days. In completers, mean weight loss was 4.6±3.5 kg or 4.7±3.5% ( p < 0.001). Physical function measures of 30-s sit-to-stand repetitions increased from 13.5±5.7 to 16.7±5.9 (p< 0.001), 6-min walk improved by 42.0±77.3 m ( p =0.005) but no differences were observed in gait speed or grip strength. Subjective measures of late-life function improved (3.4±4.7 points, p < 0.001). Conclusions A technology-based obesity intervention is feasible and acceptable to older adults with obesity and may lead to weight loss and improved physical function. Clinical trial registration Registered on Clinicaltrials.gov # NCT03104205 . Registered on April 7, 2017. First participant enrolled on October 1st, 2018.